CONDITION OF WATER RESOURCE IN INDONESIA AND ITS ENVIRONMENTAL TECHNOLOGY - Kardono, Kardono (Jurnal Air Indonesia, 2007)
Water resource is one of the most important resources for life and development. In Indonesia, the increasing population and development results the increased demand of water. On the other hand, water resource availability has become limited and has been at critical level for several locations. Around 65% Indonesian population (~ 125 Million people) live in Java island which is only 7% of total Indonesia continental area. The decrease of water resource is caused by some factors, namely pollution, deforestation, heavy agricultural activities, and the change of the function of catchment area. This paper will give some brief description how water resource in Indonesia distributes and what the appropriate technologies have been used for the treatment of low quality of water in order to fulfill the human life needs. Keywords: water resource, pollution, climate change, health impact.